Study of Symbiont Bacteria of Acropora digitifera Coral From Ciletuh Bay, Sukabumi by Using Culture and Molecular Approach - Nurfitri Nurfitri; Fiddy Semba Prasetiya; Indah Riyantini; Yuniar Mulyani; Sulastri Arsad; Mochamad Untung Kurnia Agung (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2019)
Bacteria are one of the prokaryotic microorganisms that are symbiotic with coral reefs. These microorganisms help corals in secreting mucus layers which are used as a place to live for bacteria and control the presence of pathogenic bacteria in corals. The purpose of this study was to determine the diversity of bacterial communities associated with Acropora digitifera corals in Ciletuh bay, West Java, by culture approach. Sampling was carried out at a depth of 4 meters. Morphology-based identification and molecular approach based on sequence of the small ribosomal unit (16S) rRNA gene were used to determine the bacterial species in the samples. A total of six pure isolates were identified based on morphological observation and the molecular DNA characteristics from three of them were identified with 16S rRNA gene sequences. The identification using 16S rRNA gene showed that the isolate ACD.P4.PH7.P had a close relationship with the BF strain and zb strain of Bacillus flexus (acc number MH569560.1) with a similarity of 85.44 %. While ACD.P4.PH9.P isolate has a close relationship with Bacillus sp. c234 (acc number FJ950647.1) with a similarity of 98.50 %. Additionally, ACD.P4.PH9.K isolates closely related to Bacillus sp. of strain 6RM1 (acc number MK134607.1) with a similarity of 94.78 %. This study also revealed that both microscopic identifications by morphological traits and molecular approach using 16S rRNA gene can be used in bacterial diversity assessment.